Weight matters: exploring the relationship between BMI status and glycemic control in diabetic patients - Eva, Israt Zerin; Afrooz, Farhana; Qureshi, Nazmul Kabir; Ferdous, Chandina (International Journal of Research in Medical Sciences, 2024)
Background: In the management of diabetes mellitus, understanding the interplay between body weight and glycemic control is crucial. The relationship between BMI status and glycemic control among diabetic patients is multifaceted and pivotal for optimizing treatment strategies and reducing complications. This study aims to assess the relationship between BMI status and glycemic control in diabetic patients. Methods: This study was a cross-sectional design to assess the relationship between BMI status and glycemic control in diabetic patients conducted from November 2022 to October 2023 at National Healthcare Network (NHN), Uttara, Dhaka, Bangladesh. Data were collected from patient medical records and structured interviews, focusing on the fasting blood glucose (FBG) levels, HbA1C%, and body mass index (BMI). Pearson correlation coefficients were calculated to assess the strength of linear relationships between BMI, HbA1C, and glycemic control measures, with statistical significance set at p<0.05. Results: In the study, for BMI 18-24, 60% had normal fasting blood glucose, while 67.9% had elevated levels; 64.0% had HbA1C <7%, and 67.6% had ≥7%. In BMI 25-30, 30% had normal fasting blood glucose, 16.7% had elevated levels, 25% had HbA1C <7%, and 18.7% had ≥7%. For BMI >30, 10% had normal fasting blood glucose, 15.4% had elevated levels, 12% had HbA1C <7%, and 13.7% had ≥7%. Conclusions: A significant association was found between BMI status and glycemic control among diabetic patients. Higher BMI is correlated with poorer glycemic control, as indicated by elevated fasting blood sugar and HbA1C% levels. These findings emphasize the importance of weight management as a crucial component of diabetes care to achieve better glycemic control and reduce the risk of complications.